Piloting a gender-responsive tool for assessing the poverty impacts of value chain development - Stoian, D.; Meldrum, G.; Elias, Marlène (Bioversity International and the International Center for Tropical Agriculture, 2016)
Field researchers from three parts of India participated in a training workshop on a new gender-responsive methodology for assessing the poverty impacts of value chain development - 5Capitals-G.